ASSESSMENT OF STUDENT'S INTERESTS AND TALENTS USING THE WEB-BASED CERTAINTY FACTOR METHOD - Satryanto Andi Seputro; Fajar Masya (Jurnal Riset Informatika, 2020)
Abstract To improves a child's intelligence, it can be started from knowing the advantages possessed by children in the aspect of multiple intelligences by exploring the interests and talents of children as early as possible to develop optimally. At TK Widya Bhakti it is difficult to know the interests and talents of students because of the unavailability of assessment equipment. Therefore a study was conducted using a web-based application called AMIBA that can be used to determine the interests and talents of these students. The method used in this study is the Certainty Factor method that can measure the level of certainty. The results showed that this application can assess the interests and talents possessed by each student.